2012
DOI: 10.1002/pits.20622
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic review of the cover‐copy‐compare and variations of this self‐management procedure

Abstract: Studies that examined copy‐cover‐compare (CCC) and variations of this procedure were reviewed and analyzed. This review revealed a substantial number of studies that validated the use of CCC across spelling and math skills and across students with and without disabilities. A meta‐analysis of findings indicated that CCC and variations of this procedure were effective for helping students acquire and become fluent in academic skills. The strongest effects were evident when CCC and variations of this procedure we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…To efficiently reach these goals, interventions that result in fluent responding are needed. Fortunately, a variety of math interventions, such as cover, copy, and compare (CCC; McLaughlin & Skinner, 1996;Joseph et al, 2012), taped problems (TP; McCallum et al, 2004), and explicit timing (Clark & Rhymer, 2003;Rhymer, Henington, Skinner, & Looby, 1999), have been empirically shown to increase fluent responding to basic math facts. These interventions are successful largely because they incorporate high rates of active, accurate responding and have been shown to increase fluency across skills, populations, and settings (Skinner, 1998).…”
Section: Interventions To Increase Computational Proficiencymentioning
confidence: 98%
“…To efficiently reach these goals, interventions that result in fluent responding are needed. Fortunately, a variety of math interventions, such as cover, copy, and compare (CCC; McLaughlin & Skinner, 1996;Joseph et al, 2012), taped problems (TP; McCallum et al, 2004), and explicit timing (Clark & Rhymer, 2003;Rhymer, Henington, Skinner, & Looby, 1999), have been empirically shown to increase fluent responding to basic math facts. These interventions are successful largely because they incorporate high rates of active, accurate responding and have been shown to increase fluency across skills, populations, and settings (Skinner, 1998).…”
Section: Interventions To Increase Computational Proficiencymentioning
confidence: 98%
“…Cover, copy and compare (CCC) clearly allows individualization to take place (Joseph, Konrad, Cates, Vajcner, Eveligh, & Fishley, 2012;Merritt, McLaughlin, Weber, Derby, & Barretto, 2012;McLaughlin & Skinner, 1996;Skinner, McLaughlin, & Logan, 1997), but there is not any group choral responding with CCC. To implement this would require many procedures to change.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that such methods as cover, copy, compare or add-a-word remained highly effective for improving the spelling performance of students with learning disabilities. A meta-analysis of CCC (Joseph, Konrad, Cates, Vajcner, Eveligh, & Fishley, 2012) indicated that spelling was the most common dependent variable employed with this classroom intervention. The most common student population studied has been elementary school students in general as well as special education.…”
Section: Introductionmentioning
confidence: 99%
“…The CCC instructional method has also generated a great deal of research verification and has been employed across a wide variety of curricular areas and disability designations (Ivicek-Cordes, McLaughlin, Derby, & Higgins, 2012;Joseph et al, 2012;McLaughlin & Skinner, 1996;Skinner, McLaughlin, & Logan, 1997). This self-managed academic intervention, the cover, copy, and compare procedure is student-paced and participant evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation